Energy metabolism during 400 and 100-m-crawl swimming: Computer simulation based on free swimming measurement - Rodriguez, F.; Mader, A. (Biomechanics and Medicine in Swimming IX, 2003)
This study aimed to approach the relative contribution of the energy delivery systems during 400 and 100-m events by simulating the dynamic behaviour of the energy metabolism during swimming on the basis of field metabolic measurements in young competitive swimmers. Ten swimmers of national level (5 M, 5 F) performed a series of five unimpeded 400-m swims (ca. 75-100 % Vmax) and a maximal 100-m swim in a 50-m pool. Oxygen uptake was measured breath by breath (CPX II, Medical Graphics, USA) during the immediate recovery period (Rodríguez 1999). Blood lactate was analysed in serial capillary samples (Boehringer-Mannheim, Germany). Averaged metabolic measurements for every swim were introduced into a computer simulation model (CS) based on a system of differential equations to simulate the dynamics of energy muscle metabolism (Mader & Heck 1994). The dynamic CS estimations showed that the aerobic energy supply clearly exceeds values commonly found in the literature for 400 m (ranging from ca. 25-60 % Etot), as well for 100 m events (ca. 5-20 % Etot). The relatively high maximal aerobic and low glycolytic power of the subjects (most of them middle-distance swimmers) partially accounts for high contribution of the oxidative sources. However, the relevance of the aerobic contribution to total energy demands should not be underestimated, particularly in young swimmers.